Dose Variations Using an X-Ray Cabinet to Establish in vitro Dose-Response Curves for Biological Dosimetry Assays - Bucher, Martin; Weiss, Tina; Endesfelder, David; Trompier, Francois; Ristic, Yoann; Kunert, Patrizia; Schlattl, Helmut; Giussani, Augusto; Oestreicher, Ursula (Frontiers in Public Health, 2022)
In biological dosimetry, dose-response curves are essential for reliable retrospective dose estimation of individual exposure in case of a radiation accident. Therefore, blood samples are irradiated in vitro and evaluated based on the applied assay. Accurate physical dosimetry of the irradiation performance is a critical part of the experimental procedure and is influenced by the experimental setup, especially when X-ray cabinets are used. The aim of this study was to investigate variations and pitfalls associated with the experimental setups used to establish calibration curves in biological dosimetry with X-ray cabinets. In this study, irradiation was performed with an X-ray source (195 kV, 10 mA, 0.5 mm Cu filter, dose rate 0.52 Gy/min, 1st and 2nd half-value layer = 1.01 and 1.76 mm Cu, respectively, average energy 86.9 keV). Blood collection tubes were irradiated with a dose of 1 Gy in vertical or horizontal orientation in the center of the beam area with or without usage of an additional fan heater. To evaluate the influence of the setups, physical dose measurements using thermoluminescence dosimeters, electron paramagnetic resonance dosimetry and ionization chamber as well as biological effects, quantified by dicentric chromosomes and micronuclei, were compared. This study revealed that the orientation of the sample tubes (vertical vs. horizontal) had a significant effect on the radiation dose with a variation of −41% up to +49% and contributed to a dose gradient of up to 870 mGy inside the vertical tubes due to the size of the sample tubes and the associated differences in the distance to the focal point of the tube. The number of dicentric chromosomes and micronuclei differed by 30% between both orientations. An additional fan heater had no consistent impact. Therefore, dosimetric monitoring of experimental irradiation setups is mandatory prior to the establishment of calibration curves in biological dosimetry. Careful consideration of the experimental setup in collaboration with physicists is required to ensure traceability and reproducibility of irradiation conditions, to correlate the radiation dose and the number of aberrations correctly and to avoid systematical bias influencing the dose estimation in the frame of biological dosimetry.